PENGARUH MENGKONSUMSI KOMBINASI JUS BUAH BIT (BETA VULGARIS) DAN JAMBU BIJI (PSIDIUM GUAJAVA.L) TERHADAP KADAR HAEMOGLOBIN (HB) MAHASISWA PRODI D III KEBIDANAN SEKOLAH TINGGI ILMU KESEHATAN KUNINGAN - anggit kartikasari (Ikatan Bidan Indonesia (IBI), 2020)
Young women as a mother to be if anemia while pregnant and childbirth will be very dangerous both for pregnancy and during chilbirth. Young women who have anemia when being pregnant are at risk of childbirth with low birth weight (BBLR) and stunting. Beetroot (Beta Vulgaris) is one of fruits that is often used as a natural dye for different types of food, high potency folate to prevent heart disease and anemia. The purpose of this research is to know the effect of consuming combination of beetroot (beta vulgaris) and guava juices (psidium guajava.l) against hemoglobin levels. The stages of research include the preparation, implementation, and collection of data conducted in Institute of Health Science Kuningan. Design research using Quasi-Experimental design with Nonequivalent Comparison Group Design. The free variable in this research is the consumption of beetroot juice (beta vulgaris) and the bound variabel is hemoglobin levels. Sampling techniques using purposive sampling. Analysis used is univariate analysis and bivariate analysis with Paired T-Test. The results showed that the p-value of the treatment group was 0,001, meaning that there is a effect of consuming combination of beetroot juice and guava juice on hemoglobin levels, while the p-value of the control group was 0,138 means that there is no effect on the control group hemoglobin levels Keywords : beetroot, guava, hemoglobin levels